Analysis Policy Campus Finance : Opportunities and Challenges STIE Ganesha Case Study - Rita, Rita (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
Policy finance campus play role strategic in ensure sustainability operational and quality education high . This study aiming For analyze opportunities and challenges faced​ college tall in design and implement policy adaptive and sustainable finance . Approach​ qualitative used with to study literature , secondary data , and studies case from a number of institution education high in Indonesia. The results of the analysis show that digitalization finance , diversification source funding , and collaboration with sector private open opportunity big for autonomy and efficiency campus fund management . However Thus , the challenge main covering transparency budget , dependence on government funds , and resistance to change internal policies . This study recommend strengthening governance​ finance campus through system transparent reporting , improvement​ capacity managerial , as well as approach based on risk For support taking strategic decisions . Findings​ This expected become reference for the takers policies in the sector education tall.